Pengaruh Kompetensi, Independensi, Profesionalisme dan Pengalaman Kerja Auditor terhadap Kualitas Audit (Studi Empiris pada Kantor Akuntan Publik di Kota Medan) - Simanullang, Yuni Yessilia S.; Saribu, Ardin Dolok; Sihombing, Halomoan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to partially determine the influence of professionalism, independence, competence and work experience of auditors on audit quality in Public Accounting Firms. The sample used in this research was auditors who worked at the Medan City Public Accounting Office. The sampling technique in this research was carried out using a purposive sampling method so that 7 Public Accounting Firms with a total of 40 Auditors were obtained. The data obtained in this research is primary data through distributing closed questionnaires to auditors working at KAP Medan who are registered in the Directory of the Indonesian Institute of Public Accountants and the research method used is multiple linear regression analysis. From the results of hypothesis testing, it can be concluded that auditor competence and auditor professionalism have a positive but not significant effect, independence has a positive and significant effect, while work experience has a negative and significant effect. This is shown through the results of the t-test which shows a significant relationship with the variables with a significance rate of 5%.